Immigrants from eastern partnership (EaP) countries in Spain - Lídia Farré; Núria Rodríguez-Planas (IZA Journal of European Labor Studies, 2014)
Most EaP migrants in Spain come from Ukraine, followed by, to a much lesser extent, Moldavia, Armenia, and Georgia. Relative to other migrants, they are those who most recently arrived to Spain. Using data from Spanish Labor Force Survey (LFS) from the years 2000 to 2011, this paper analyzes how their employment situation evolves with time in Spain, the type of sectors they work in, and their welfare use, including unemployment insurance receipt. We find that the employment rate of EaP migrants is similar to that of the natives. This is because although they face an employment penalty upon arrival, they catch up quickly. In addition, we document that EaP migrants, despite their higher educational level, are less likely to work than natives and other migrant groups upon arrival to Spain. However, the initial disadvantage in terms of employment and working conditions dissipates over time. We also find that their use of welfare increases with experience in the country.
Keywords: J61; J15; 330; Immigrant assimilation and Eastern Partnership countries